CORRELATION OF THE USE LEARNING REPORT APPLICATION AND AUTHENTIC ASSESSMENT OF 2013 CURRICULUM ON ELEMENTARY TEACHERS’ PERFORMANCE IN BANTUL REGENCY - Himawan Sulistyo (Universitas PGRI Yogyakarta, 2022)
This research aims to analyze the relationship of using the student report application and the authentic assessments of curriculum 2013 to the elementary school teachers’ performance in Bantul regency. The main background for conducting this research is because the majority of teachers in Bantul Regency have used this application in their assessment. This research uses the survey method for elementary school teachers in Kapanewon Kasihan, Bantul Regency. The research sample is taken using a simple random sampling technique of 150 teachers among the whole 240 elementary school teachers This research uses a quantitative approach with correlational descriptive, and the instrument in this research was a questionnaire using a Likert scale model through the Goggle Form online. The data is processed in the multiple linear regression analysis method tabulated with the SPSS for version-26 Windows program. The hypothesis test uses the product moment correlation which previously carried out pre-requisite tests which included normality test, homogeneity test and linearity test. The results showes that: (1) there is a significant relationship between the students report application and teacher performance, based on the hypothesis test results, a correlation value of 0.762 is obtained with a sig value of 0.000 <0.05; (2) there is a significant relationship between authentic assessment and teacher performance, this is based on the results of the hypothesis test which obtaines a correlation value of 0.757 with a sig value of 0.000 <0.05; (3) there is a significant relationship between the use of student report application and the implementation of authentic assessment applied together on the performance of elementary school teachers with a double correlation value of 0.857 and R Square of 73.4%. The result of this research indicates that there is a positive and significant relationship between the student report application and authentic assessments with the performance of elementary school teachers in Kapanewon Kasihan, Bantul Regency.